Variants in the fetal genome near pro-inflammatory cytokine genes on 2q13 associate with gestational duration - Xueping Liu (Nature Communications, 2019)
Gestational duration depends on both maternal and fetal genetic influences. Here, the authors perform a fetal genome-wide association meta-analysis and find that a locus on 2q13 is associated with pregnancy duration and further show that the lead SNP rs7594852 changes the binding properties of transcriptional repressor HIC1.